The chromatin remodeller ATRX: a repeat offender in human disease. - Clynes, D; Higgs, D; Gibbons, R (Cell Press, 2013)
The regulation of chromatin structure is of paramount importance for a variety of fundamental nuclear processes, including gene expression, DNA repair, replication, and recombination. The ATP-dependent chromatin-remodelling factor ATRX (α thalassaemia/mental retardation X-linked) has emerged as a key player in each of these processes. Exciting recent developments suggest that ATRX plays a variety of key roles at tandem repeat sequences within the genome, including the deposition of a histone variant, prevention of replication fork stalling, and the suppression of a homologous recombination-based pathway of telomere maintenance. Here, we provide a mechanistic overview of the role of ATRX in each of these processes, and propose how they may be connected to give rise to seemingly disparate human diseases.